INTERAKSI SIMBOLIKPENGGUNAAN NAPZA OLEH MAHASISWA DI KOTA MALANG - Muhammad Mukhlis Anshori; Alfin Nur Laili; Taufiqur Rohman Muzakki; Bambang Soepeno; Sukidin (Universitas Andalas, 2025)
The use of Narcotics, Psychotropics, and Addictive Substances (Napza) among students is an important issue in the context of health and behavior. Head of General Affairs of the Malang City BNN, Benny Trianto, in his interview on September 11, 2024 emphasized that drug abuse in Malang does not only target students, but has also spread to students. This is very concerning for the future of the Indonesian nation. Drug users among private students in Malang City use certain symbols in interactions with other users. This study focuses on the reasons why students of Private Universities in Malang City use drugs, the symbols used by students, and how these symbols are communicated. The descriptive qualitative research method with observation techniques, in-depth interviews, and documentation was then analyzed descriptively. This study reveals two main factors that influence students in Malang City to use drugs: internal factors such as emotional pressure, stress, boredom, and curiosity, and external factors such as the friendship environment at home, campus, and free association. Symbols in the interactions of drug users are formed through social processes and play a role in communication and identity. Terms such as SS, Micin for crystal meth, and cat, live, white, rice for Trihexyphenidyl are only understood in the user environment. Physical symbols such as prohibition posters, liquor bottles, and dim lighting also reflect their identity and lifestyle.